Monte carlo methods for particle transport - Haghighat, Alireza (Crc Press, 2015)
The Monte Carlo method has become the de facto standard in radiation transport. Although powerful, if not understood and used appropriately, the method can give misleading results. Monte Carlo Methods for Particle Transport teaches appropriate use of the Monte Carlo method, explaining the method's fundamental concepts as well as its limitations. Concise yet comprehensive, this well-organized text: introduces the particle importance equation and its use for variance reduction; describes general and particle-transport-specific variance reduction techniques; presents particle transport eigenvalue issues and methodologies to address these issues; explores advanced formulations based on the author's research activities; discusses parallel processing concepts and factors affecting parallel performance.